Carbon dioxide mitigation using mutant Synechoccus PCC 7002 enhanced by aqueous ammonia - Azmi, Azlin Suhaida; Awan, Mohamed Anwar (2015)
Anthropogenic carbon dioxide (CO¬2¬) has been identified as one of the major causes of global warming with atmospheric levels having presently reached 400 ppm. This study is centered on investigating the prospects of utilizing and enhancing the well-understood natural photosynthetic process in marine cyanobacteria with the purpose reducing carbon dioxide emissions, and as such taking a step towards preserving our world for future generations. The study concentrates on using aqueous ammonia to enhance cyanobacterial carbon dioxide biomitigation. The objectives of the study were to identify conditions that would maximize carbon dioxide mitigation. The study used mutant strain of cyanobacteria (Synechococcus PCC 7002) in batch cultures. The CO2 mitigation were conducted under varying conditions of CO2 flow rate, absorption temperature and aqueous ammonia concentrations. The effectiveness of the cyanobacteria was quantified by measuring the cell concentration and percentage reduction in carbon dioxide concentration, while the biofuel production potential was quantified by measuring the lipid content. The overall results of the experiment identified the conditions to enhance CO2 biomitigation while sustaining growth optimally and being a potential biofuel source to be 0.5 Lpm CO2 flow rate, 0.75 % (w/v) ammonia concentration and a temperature of 33°C.